Using New Data to Support Tax Treaty Negotiation - World Bank (World Bank, Washington, DC, 2021)
This paper introduces the new Tax Treaties Explorer dataset, developed with support from the World Bank and the G-24, and illustrates its use for research by tax treaty negotiators, policy makers, and researchers. The new dataset provides a rich source of data to reexamine existing tax treaty policy, inform negotiation positions, and assess treaty networks. For the first time, it provides a tool to analyze trends in the content of tax treaties, across individual agreements, over time, and between countries. To illustrate the value of such an approach, we replicate a study by Barthel, Busse, and Neumayer (2009), which found a positive association between the presence of a tax treaty and the bilateral stock of FDI. We show that this effect is mainly driven by the withholding tax rates in the treaty rather than by other provisions affecting taxing rights such as permanent establishment. If the outcomes of this proof-of-concept replication are borne out in future research, this would suggest that negotiators can seek the maximum protection of source taxing rights in other parts of the treaty, knowing that this is unlikely to dilute investment-promoting impacts.